Fronto-Temporal N200 Event-Related Component in Dyslexic Malay Children During Audio–Visual Paired Stimuli - Siti Atiyah, Ali; Tahamina, Begum; Faruque, Reza; Nor Asyikin, Fadzil; Faiz, Mustafar (Fakulti Perubatan dan Sains Kesihatan, UPM PRESS, 2021)
Introduction: Shifted attention can be studied in paired stimuli using different experimental paradigms. Pre-existing literatures showed that children with dyslexia have difficulty in learning. Hence, there might be a relationship between learning difficulty and shifted attention. We investigated shifted attention and topographic distribution of the N200 component using audio–visual paired stimuli in an event-related potential (ERP) study among dyslexic Malay children. Methods: A 128 ERP net designed for children was used for the study. A total of 24 age-matched children were divided into control (n=12) and dyslexic (n=12) groups. A modified audio–visual paired stimuli paradigm was used for the ERP study. Congruent (animal-matched sound) and incongruent (animal-not matched sound) stimuli were used. All participants were instructed to press key ‘1’ and ‘2’ when congruent and incongruent stimuli are presented, respectively. Amplitudes and latencies of the N200 ERP component were analysed at 19 electrode locations in the 10-20 system. A topographic map was analysed for the N200 component for both groups. Results: There was no significant differences in the N200 amplitudes and latencies between children with dyslexia and control children at any sites. The topographic map distribution revealed that the dyslexic group had right frontal and left temporal N200 voltage distribution during the incongruent stimuli. Conclusion: We conclude that Malay children with dyslexia have no difficulties/intact in shifted attention. Moreover, children with dyslexia have diverted left temporal areas during auditory sound attention.